An exploration of communication within active support for adults with high and low support needs. Issue 1 (27th June 2018) - Iacono, Teresa; Bould, Emma; Beadle‐Brown, Julie; Bigby, Christine
Abstract: Background: The aim was to explore the relationship between quality of active support and communication support for people in group homes with high and low support needs. Methods: Data from 182 service users, 20–81 years (mean = 40), 89 with high support needs, were observed to have either good ( n  =   142) or poor ( n  =   40) communication support. Measures were of quality of active support, engagement and staff contact; field notes provided examples of good and poor communication supports. Results: We found a relationship between the quality of communication support and active support. Receiving good communication was associated with higher levels of engagement. Field notes included some examples of appropriate communication supports, but limited use of augmentative and alternative communication (AAC). Conclusions: Staff show limited use of appropriate communication with people having high support needs who require AAC. Strategies to improve quality of practice are discussed.